Living on the Level: Horizontally-planned Lodgings in Fifteenth- and Early Sixteenth-Century Scotland. Issue 1 (November 2015) - Oram, Richard D.
Abstract : Horizontally integrated public spaces and private accommodation in enfilade (i.e. entered in sequence one from another) were presented by Charles McKean as the successor in Scottish elite planning from around the 1520s to the vertically disposed provision of earlier towers. 1 Architectural innovation there certainly was in what is often labelled Scotland's early Renaissance period, and the efflorescence of buildings of this basic plan within houses of the Scottish nobility from the late 1530s onwards suggests an enthusiastic embracing of the new prescription for elite living that it offered. This article argues, however, that, rather than being a new departure of the 1500s, such buildings were present by the later fifteenth century, already forming the principal apartments of major courtyard 'palace' complexes in both royal and lordly contexts, and as an architectural expression of power they have too often been literally overshadowed by towers.